A Criminological Analysis of Social and Economic Factors Triggering Criminal Acts in Urban and Rural Areas - Purnama, Devina Mayra; Mursid, Sri Rizka Novi Anggraeni; Rahayu, May Riski Anita; Nuraeni, Henny; Ma'arif, Rizal Syamsul (Riviera Publishing, 2025)
Criminal acts in urban and rural areas are influenced by differing social and economic factors. This research aims to analyze the primary triggers of criminal behavior in both types of regions. Employing a qualitative approach, the research utilizes in-depth interviews and participatory observations to gain an understanding of the social and economic dynamics that contribute to crime rates. The results reveal that in urban areas, economic factors such as unemployment and poverty are the dominant drivers of criminal acts. In contrast, in rural areas, social factors such as inter-community tensions and limited access to education play a more significant role. These results offer important insights for governments and policymakers in formulating contextual and effective crime prevention strategies that are tailored to the specific characteristics of each region.